Penerapan Model Pembelajaran Kooperatif Group Investigation (GI) dalam Meningkatkan Prestasi Belajar Siswa Kelas VII SMP Negeri 1 Keruak - Irwan Yon Hadi (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2024)
Education is defined as a business consciously done by humans to increase the quality of self so that capable people build themselves, their religion, their nation, and their country. More specifically, education is business conscious and planned for realizing atmosphere learning and the learning process for participants educate in a way active develop potency himself for own religious spiritual power, control self, personality, intelligence, morals noble, as well necessary skills himself, society, nation, and state. Study This aims to know the application of the Learning Model Cooperative Group Investigation (GI) in Improving Performance Study Student Class VII of Keruak 1 Public Middle School. The type of research used is study action class (PTK). The data obtained from activity observation from every cycle was analyzed in a way descriptive with the use of technique percentage to see a trend that occurs in the learning process. Subject study this is student Class VII of SMPN 1 Keruak, totaling 30 people. The research results obtained from cycle I ie 18 students completed, and no 12 people completed. The average activity score of 10.37 students was categorized as Enough active, complete Study obtained 60% with an average score of 63.83 with amount 18 students completed. In cycle II the average activity for students was 12.33 with the category active whereas the completeness Study by 90% with amount 27 students completed. From the results data analysis can concluded that the application of learning models Group Investigation (GI) can increase the performance of Study Student Class VII at SMPN 1 Keruak.